Analysis of the impact of the COVID-19 pandemic on financial reporting and financial performance (Case of Jordan) - Shaqqour, Omar Fareed (Asian Economic and Financial Review, 2025)
The research aims to analyze the impact of the COVID-19 pandemic (CP) on financial reports and financial performance (FP). The analytical approach was followed through a study model that shows the independent variable (CP) and the dependent variable (FP). To achieve the study’s objectives, three indicators were used to measure the dependent variable (FP): the return on assets rate (ROA), the financial leverage ratio, and the company growth rate. The independent variable (CP) was measured by comparing the FP of companies listed on the Amman Stock Exchange (ASE) before and during the CP. The study was conducted on companies listed on ASE for the year 2021, for which the data required to implement this study is available, represented in the financial statements of companies listed on ASE during the period 2019-2020, with a total of 149 companies. The results indicated that the CP impacted ROA, leverage ratio, and growth rate in the services sector, while no impact was observed in the industrial and financial sectors of ASE. The study also showed that the impact of CP on ROA varied according to the company sector.